An Analysis of Professional Teachers’ Questions in EFL Classroom - Shelly Navtria; Mulyadi Mulyadi; Hilda Puspita (Jadila: Journal of Development and Innovation in Language and Literature Education, 2020)
In English language classroom, teachers’ questions are important parts of teaching English language. Teachers need to know what kind of questions which potentially support students learning the target language. However, students did not actively participate in learning particularly when responding to teachers’ questions. To overcome this problem, it is important for teachers to modify their questions through some techniques in order to get students’ responses. This study reports the types of teachers’ questions used by English teachers in the classroom. This research was descriptive quantitative research. The research was conducted at the tenth grade of SMA N 5 Bengkulu. The data were collected through observation and video recording. The teachers’ questions were analyzed using types according to Taxonomy Blooms revised by Anderson and Krathwohl (2001). The research findings show that both teachers the English teachers only used three from the six types. Namely, remembering, understanding, and analyzing questions. The types that did not appear were applying, evaluating, and creating questions. The modification of modifying questions are repeating and rephrasing. The dominant of remembering questions and how teachers modified the questions are influenced by teachers’ competence, students’ competence, a situation of teaching English language, and teaching material.